Effect of Local Microorganisms from Calamansi Peel and Banana Peel Addition on the Quality of Liquid Organic Fertilizer (POC) Produced from Tofu Wastewater (Universitas Muhammadiyah Prof. Dr. Hamka, 2026)
Background: Bengkulu Province has seen a significant rise in calamansi orange (Citrus microcarpa) cultivation since 2010. While popular for their unique aroma and high flavonoid content (including ascorbic and citric acids), they also generate significant byproduct potential. To optimize the quality of Liquid Organic Fertilizer (POC) derived from this waste, specific additives are required to ensure the final product meets established quality standards. Tofu wastewater is an organic by-product with potential for use as liquid organic fertilizer. This study aimed to determine the effect of adding local microorganisms derived from calamansi peel and banana peel on the nutrient quality of liquid organic fertilizer produced from tofu wastewater. Methods: The measured parameters were nitrogen (N), calcium (Ca), phosphorus (P), and potassium (K). This study used an experimental design with four treatment groups: control, 1 kg, 2 kg, and 3 kg additions of fruit peel-based materials. Data were analyzed using one-way ANOVA. Results: The highest values of N, Ca, P, and K were observed in the 3 kg treatment, at 0.56%, 0.18%, 0.42%, and 0.42%, respectively. Statistical analysis showed significant differences in N, Ca, and K contents among treatments, whereas P content did not differ significantly. Conclusions: These findings indicate that the addition of calamansi peel and banana peel materials influenced several nutrient parameters of the liquid organic fertilizer, although not all parameters met the expected quality standard